Response of T. Aman Rice (Oryza sativa L.) to S, Mg, Zn, B, Mo and Organic Amendments in Tista Meander Floodplain Soil (The Agriculturists, 2010)
A field experiment was conducted at the BINA sub-station of Tajhat, Rangpur in the Tista Meander Floodplain soil during aman season 2003 to study the response of T. aman rice to S, Mg, Zn, B, Mo and organic amendments. The experiment was laid-out in a randomized complete block design with nine treatments is with three replications as T1: complete (S + Mg + Zn + B + Mo), T2: completeS, T3: completeMg, T4: completeZn, T5: completeB, T6: completeMo, T7: cowdung @ 5 t/ha, T8: poultry manure @ 5 t/ha and T9: control. Nitrogen, phosphorus and potassium were applied in recommended doses as basal. The highest grain (3927 kg/ha) and straw (4472 kg/ha) yields were recorded with the application of poultry manure, followed by cowdung and complete (S+Mg+Zn+B+Mo) treatment. The lowest yield was recorded in the control plot. The overall results indicate that application of organic amendments with NPK gave satisfactory yield of T. aman rice in the Tista Meander Floodplain Soil.